Excess Enthalpies of Mixing of Binary Mixtures of Isopropyl Benzene with Ethyl Acetate and Butyl Acetate at 298.15 K - Singh, Sukhmehar; Rattan, V.K.; Sharma, S.K. (Asian Journal of Chemistry, 2016)
The excess enthalpies of mixing of two binary systems isopropylbenzene with ethyl acetate and butyl acetate have been experimentally determined using a Tronac-1250 isoperibol calorimeter at 298.15 K. Both the systems are endothermic in nature over the whole composition range. Three group contribution models, the UNIFAC, the UNIFAC-II and the ASOG, have been used to predict the enthalpies of mixing for the systems and are then compared with experimental values. It is observed that predictions by the ASOG and UNIFAC-II models are in close agreement with the experimental data for both the systems.